TINJAUAN PUSTAKA PENGARUH TEKNOLOGI DAN MEDIA SOSIAL TERHADAP SPIRITUALITAS UMAT KRISTEN - Densa Tale'; Elentika, Gilbert Agryan Dwinata, Yetri Pani Sambalangi', Monica Dei (ADISAM PUBLISHER, 2023)
This research aims to investigate the impact of the use of technology and social media on the spiritual experience of Christian believers in the contemporary context. With the rapid development of information technology and the widespread use of social media, questions about how this affects the spiritual dimensions of the lives of Christians become increasingly relevant. This literature review focuses on the analysis of various sources that encompass key aspects of the interaction between technology, social media, and spiritual experience. Firstly, the research explores how Christians use social media as a channel to participate in spiritual activities such as prayer, online worship services, and electronic or digital Bible reading. Subsequently, the study considers the impact of forming spiritual identity online and how the use of social media can shape individual perceptions of faith and spiritual practices. The analysis also involves considerations of ethics and morality related to the use of spiritual technology, including issues such as privacy, the reliability of spiritual teachings, and the impact of influential spiritual figures in the online world. The research also discusses changes in church engagement through technology, considering how churches utilize social media to communicate, convey spiritual messages, and facilitate community interaction. Thus, this research strives to provide deeper insights into the role of technology and social media in shaping and transforming the spiritual experience of Christian believers in this digital era.